2002
DOI: 10.1089/107999002320271341
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 Directly Induces Activation and Proliferation of Chicken T CellsIn Vivo

Abstract: Cytokines, as immune activators, have been investigated in mammalian systems as natural adjuvants and therapeutics. In particular, interleukin-2 (IL-2) has been studied widely as a vaccine adjuvant and immuno-enhancer because of its role in activating T cell proliferation. We show here that the first nonmammalian IL-2 gene cloned, chicken IL-2 (ChIL-2), exhibits similar biologic activities to those of mammalian IL-2. To assess the activities of ChIL-2 in vivo, we injected birds with recombinant ChIL-2 (rChIL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Th1 cells are characterized by the secretion of IFN-γ, IL-2 and IL-12p40, and a strong cell-mediated immunity that is geared towards effective elimination of intracellular pathogens such as viruses [17]. IL-2 stimulates proliferation of chicken T lymphocytes and NK cells [24-26]. Production of IL-12 and IFN-γ is critical to host defense against intracellular pathogens [27], indicating that it is possible to observe simultaneous up-regulation of IFN-γ and IL-10 in response to IBDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Th1 cells are characterized by the secretion of IFN-γ, IL-2 and IL-12p40, and a strong cell-mediated immunity that is geared towards effective elimination of intracellular pathogens such as viruses [17]. IL-2 stimulates proliferation of chicken T lymphocytes and NK cells [24-26]. Production of IL-12 and IFN-γ is critical to host defense against intracellular pathogens [27], indicating that it is possible to observe simultaneous up-regulation of IFN-γ and IL-10 in response to IBDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…ConA activation of T cells also induces cell-surface expression of chIL2R [43]. The interaction between IL2 and its receptors stimulates the growth, differentiation, and survival of antigen-selected cytotoxic T cells by autocrine or paracrine methods [1].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to immune function of IL-2 in mammalls, ChIL-2 can directly induce activation and proliferation of chicken T cells in vivo and plays an important role in enhancing the immunogenicity of vaccines (Hilton et al, 2002;Kogut et al, 2002). We have recently shown that the plasmid encoding ChIL-2 (pCI-IL-2) can enhance the immunogenicity of DNA vaccine against infectious bursal disease virus (Li et al, 2004).…”
Section: Discussionmentioning
confidence: 99%